Manajemen Proyek Agile dengan Pendekatan Metode Scrum sebagai Peningkatan Layanan Berkelanjutan Perusahaan - R Wisnu Prio Pamungkas; Rakhmi Khalida (Ikatan Ahli Informatika Indonesia, 2019)
At present, there are many frameworks used in implementing IT Governance. But with the pattern of implementation of sustainable IT Governance development, there needs to be preparation, planning and development that carry out relatively short activities. Especially the existence of a framework that can support this activity. Therefore the author will discuss the development of IT Governance by utilizing the ITIL framework as a Continual Service Improvement by implementing more adaptive and relatively short daily activities through the design and development of using Agile Project Management with the Scrum method. So that the development of IT Governance is expected to be faster and more agile in optimizing the fulfillment of excellent service for all institutions.